Anesthesia for Endovascular Therapy for Stroke - Arianna Gaspari; Giulia Vaccari; Federica Arturi; Gabriele Melegari; Stefano Baroni (Neurology International, 2024)
Background: In patients with acute ischemic stroke, the standard of care is to perform intra-arterial endovascular thrombectomy in addition to intravenous thrombolysis. In this study, we investigated the different anesthetic techniques chosen for this procedure and clinical outcomes. Methods: Patients undergoing endovascular procedures were divided into three groups. The first group consisted of patients who received general anesthesia, the second group underwent the procedure under conscious sedation and local anesthesia at the catheter insertion site, and lastly the third group included patients who received only local anesthesia at the catheter insertion site, without sedation. Results: During the endovascular procedure, we did not notice significant differences in vital parameters, in particular the mean blood pressure (MAP) between patients treated with different types of anesthesia. Also, the duration of the revascularization did not show significant differences between the three groups. The main point is the absence of differences in terms of functional and clinical outcomes, using various scores as reference, such as the National Institutes of Health Stroke Scale (NIHSS) score at 7 days, NIHSS and Modified Rankin Scale (MRS) at time of discharge, and MRS after 3 months. These scores did not show significant differences in groups treated with different types of anesthesia. Conclusions: The rate of success of the revascularization procedure is almost overlapping between patients treated with conscious sedation and general anesthesia. In addition, we did not notice significant differences between groups in terms of functional and clinical outcomes. Considering the possible usefulness of applying conscious sedation, at OCSAE of Baggiovara, an internal protocol for conscious sedation was introduced to standardize the treatment in patients undergoing endovascular procedures.